كفاءة وفعالية رقابة البنك المركزي على حسابات فروعه وآفاق تطويرها - القاضي حسين; الأمين ماهر; جوني سوران (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث الرقابة التي يمارسها البنك المركزي على فروعه وآفاق تطويرها وذلك من خلال دراسة الواقع الراهن للرقابة وإبراز عيوبه والعمل على تطويره بشكل علمي ومنهجي من خلال الاستفادة من أتمتة المعلومات وتطبيق نظام الفروع المستقلة. وقد تناول البحث المصرف المركزي بشكل عام: تعريفه، أهدافه، خصائصه، وظائفه. كما تناول مصرف سوريا المركزي وهيكله التنظيمي والرقابة التي يمارسها على فروعه وأهداف هذه الرقابة. وبناء على الدراسة السابقة فقد تم تقديم مجموعة من المقترحات والتوصيات التي تساعد على تطوير الرقابة الحالية وزيادة كفاءتها وفعاليتها، وقد تم إجراء استبيان لمعرفة موقف موظفي البنك من المقترحات المقدمة. This paper deals with the Central Bank’s monitoring of its branches and the prospects for improvement. In particular, the paper analyzes the currant status of monitoring and its shortcoming, with the particular aim of developing the Bank, both scientifically and methodologically, through automation and the application of a system of autonomous branches. Besides, dealing with the Central bank in general terms (definition, goals, characteristics, and functions), the papers examines the Central Bank’s hierarchy and its monitoring of its branches as well as the goals of that monitoring. The study concludes with a number of suggestions and recommendations that might develop existing monitoring system and enhance its efficiency and effectiveness. The attitude of the bank’s employees towards the suggestions in this paper are known through a questionnaire given to them.